Черный, Белый и Рыжий: по мотивам книг Сесила Алдина / Андрей Усачев ; [рис. С. Алдина] - Усачев Андрей Алексеевич (Мелик-Пашаев, 2012)
Экземпляры: ф.14 (2012) / Инвентарный номер: 54550 / Цена: / Сис.шифр: 84(2Рос=Рус)6-5 / Авт.знак: У 74 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-5